2007
DOI: 10.1016/j.jse.2007.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Temporal expression of 8 growth factors in tendon-to-bone healing in a rat supraspinatus model

Abstract: Growth factors play an important role in supraspinatus tendon-to-bone healing. The objective of this study was to evaluate the temporal expression of 8 different growth factors in tendon-to-bone healing in an animal model. We hypothesize that growth factors exhibit unique temporal profiles that correlate to specific stages in the acute process of the supraspinatus tendon. To test this hypothesis, rats underwent bilateral supraspinatus tendon detachment and repair. Animals were euthanized at 1, 2, 4, 8, and 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
128
0
10

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(147 citation statements)
references
References 27 publications
6
128
0
10
Order By: Relevance
“…In our one studies we observe a high concentration of TGF-β initially, which then decreased for 2 and 4 weeks and then increase massively at 8 weeks, possibly reflecting the initial inflammation and activation of cells, followed by an intermediary period and then the remodeling of the tendon with increased apoptosis of no longer necessary cells. The results are similar to those for the rat rotatory cuff (Würgler-Hauri et al, 2007), although we observe a steeper increase at 8 weeks.…”
Section: Tgf-βsupporting
confidence: 88%
See 1 more Smart Citation
“…In our one studies we observe a high concentration of TGF-β initially, which then decreased for 2 and 4 weeks and then increase massively at 8 weeks, possibly reflecting the initial inflammation and activation of cells, followed by an intermediary period and then the remodeling of the tendon with increased apoptosis of no longer necessary cells. The results are similar to those for the rat rotatory cuff (Würgler-Hauri et al, 2007), although we observe a steeper increase at 8 weeks.…”
Section: Tgf-βsupporting
confidence: 88%
“…Our results thus suggest a tightly controlled BMP-12 concentration, which possibly helps to coordinate the newly produced cells during proliferation in the early healing period. This is also seen with the rat rotatory cuff (Würgler-Hauri et al, 2007), yet we do not see an increase in concentrations after 8 weeks, again possibly reflecting the difference in both tendons.…”
Section: Bmp-12supporting
confidence: 61%
“…GDF-5 and -6 have been detected in human tendon by immunohistochemistry, especially in metabolically active cells [8,18]. During tendon to bone healing in rats, immunohistochemistry demonstrates increased expression of GDF-5, -6, and -7 [19]. Healing of the rat Achilles tendon is sensitive to mechanical loading.…”
Section: Discussionmentioning
confidence: 99%
“…Bone morphogenic protein (BMP) 12 to 14, expressed in active fibroblasts and heavily involved in de novo joint formation, were present throughout the healing process of the boneto-tendon insertion [49,57]. Seeherman et al [49] demonstrated in a full-thickness rotator cuff tear sheep model that delivery of rhBMP-12 in sponge carriers had the potential to accelerate healing of rotator cuff repairs when compared to untreated controls.…”
Section: Biology Of Bone-to-tendon Healingmentioning
confidence: 99%